2012
DOI: 10.1063/1.3679553
|View full text |Cite
|
Sign up to set email alerts
|

Densification of chemical vapor deposition silicon dioxide film using oxygen radical oxidation

Abstract: Silicon dioxide (SiO2) films formed by chemical vapor deposition (CVD) were treated with oxygen radical oxidation using Ar/O2 plasma excited by microwave. The mass density depth profiles, carrier trap densities, and current-voltage characteristics of the radical-oxidized CVD-SiO2 films were investigated. The mass density depth profiles were estimated with x ray reflectivity measurement using synchrotron radiation of SPring-8. The carrier trap densities were estimated with x ray photoelectron spectroscopy time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…Plasma-treated oxide films consist of layers with differing mass densities because near the surface, the oxide film increases in density more easily as a result of the plasma treatment. 10 Since O (1D) atoms relax to O (3P) atoms by diffusing through the oxide films, 18 the atoms have less of an affect on the film layers far from the surface. The mass density in Figure 2 is the mean value since the bonding state concentrations determined from the IR absorbance are averaged over the entire oxide film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma-treated oxide films consist of layers with differing mass densities because near the surface, the oxide film increases in density more easily as a result of the plasma treatment. 10 Since O (1D) atoms relax to O (3P) atoms by diffusing through the oxide films, 18 the atoms have less of an affect on the film layers far from the surface. The mass density in Figure 2 is the mean value since the bonding state concentrations determined from the IR absorbance are averaged over the entire oxide film.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10] Plasma treatments generate a high density of excited oxygen atoms, which react with the SiO 2 network at temperatures typically too low for oxygen molecules reaction. 11 In previous reports, it was concluded that the SiO 2 network was reconstructed by SPA plasma treatments, which led to a reduced leakage current.…”
mentioning
confidence: 99%
“…[1][2][3] We also reported that the treatments using active oxygen species generated by Ar/O 2 plasma excited by the microwave is extremely effective. 4 We clarified that the mass density of the CVD-SiO 2 film is increased and the carrier trap density of the film is decreased by the Ar/O 2 plasma treatment with X-Ray Reflectivity (XRR) analysis and X-ray Photoelectron Spectroscopy (XPS) time-dependent measurement. In addition, we also clarified that the leakage current of the CVD-SiO 2 films in metal-oxide-semiconductor (MOS) capacitors is decreased more than two orders of magnitude by the Ar/O 2 plasma treatment.…”
Section: Introductionmentioning
confidence: 98%
“…5,6 This mechanism is the same as that of the mass densification and phase transition of the bulk SiO 2 during cooling down process in ambiences containing the flux. 4 On the other hand, we presumed that the decrease in the carrier trap density is caused by the restoration of the defects with the active oxygen species because it is probable that the active oxygen species oxidize the oxygen vacancy defects in the CVD-SiO 2 film. However, the influence of the active argon species on the carrier trap center is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation